Minimally Invasive Preganglionic C2 Root Section for Occipital Neuralgia: 2 Case Reports and Operative Video. Issue 3 (18th March 2023) - Shahin, Maryam N.; Ross, Donald A.
Abstract : BACKGROUND: Occipital neuralgia is a painful condition that is believed to occur from processes that affect the greater, lesser, or third occipital nerves. Diagnosis is often made with a combination of classical symptoms, tenderness over the occipital region, and response to occipital nerve blocks. Cervical computed tomography or MRI may be obtained in multiple positions to detect any impingement. Diagnosis can be made with MRI tractography. Nonsurgical treatments include local anesthetic and steroid injections, anticonvulsant medications, botulinum toxin injections, physical therapy, acupuncture, transcutaneous electrical stimulation, cryoneurolysis, and radiofrequency ablation. Surgical treatments include greater occipital nerve decompression, C2 root section, intradural dorsal root rhizotomy, C1-2 fusion, and occipital nerve stimulation. Although stimulation has been favored in the past decade, complications and maintenance of the devices have led us to return to C2 ganglionectomy. OBJECTIVE: To report on the use of a minimally invasive technique for C2 ganglionectomy to treat occipital neuralgia. METHODS: Review demographic, surgery, and outcome data of a minimally invasive C2 root ganglionectomy used to treat to 2 patients with occipital neuralgia. RESULTS: We report on 2 patients with clinically stereotypical unilateral occipital neuralgia confirmed by greater occipital nerve block, but with no imaging correlate. Both were successfully managed by C2 ganglionectomy through an 18-mm tubular retractor and outpatient surgery. Accompanying text, still photographs, and video describe the technique in detail. CONCLUSION: Minimally invasive C2 ganglionectomy can be used to successfully treat occipital neuralgia.